arabic Types of Incantations and Spells in Mesopotamia: Types of spells and their classifications, various other spells, ritual accompanying spells - qasim, Luqman; Ismail, Khaled (Humanities Journal of University of Zakho, 2022)
The study of incantations is one of the important studies that shed light on various aspects of the details of a life lived by the ancient inhabitants of Mesopotamia, and they excelled in them throughout the historical ages. A large number of gods that manage the affairs of the universe and humans on earth and their organizations, and hold people accountable for the sins and transgressions they commit, and evil spirits and goblins that cause diseases and harm to people, and this is what prompted people to seek the help of priests and the temple to get rid of these diseases and evil spirits by The path of spells and sophistication. Also, this study sheds light and in some detail on the most important types of spells and spells that were commonly used in Mesopotamia and the ways of using them. Some of these spells were used to expel evil spirits from the patient’s body, while others were used to invalidate magic and the dangers of demons that were causing harm and diseases. For people, including toothache, headache, eye ache, and snakebite, as well as some of these incantations were used to preserve buildings, fields, cities, and other incantations that were used in Mesopotamia. Diseases that were treated by spells in Mesopotamia.